GRI G4 content index: Does it improve credibility and change the expectation–performance gap of GRI-assured sustainability reports?. Issue 5 (6th November 2017) - Mori Junior, Renzo; Best, Peter
Abstract : Purpose: Previous studies have argued that the incapacity of the majority of SR stakeholders to identify the different types of assurance processes contributes to the existence of an expectation–performance gap and affects the credibility of such reports. To improve this situation, the Content Index Model was updated by the Global Reporting Initiative (GRI) in its latest sustainability reporting guideline – "G4". This paper aims to assess, using a qualitative exploratory approach, whether this updated Content Index Model changes the expectation–performance gap of stakeholders on assurance processes for GRI sustainability reports. This paper also assesses whether this Content Index Model improves the credibility of the assurance processes for GRI sustainability reports, considering participants' points of view. Design/methodology/approach: This paper used a qualitative approach to obtain participants' perceptions in relation to the objectives of the paper. Two questions were used to assess whether the updated Content Index Model improves stakeholders' understanding in regards to the assurance process of GRI sustainability reports, thus changing the expectation–performance gap and improving the credibility of GRI sustainability reports. The following questions were asked: Does the Content Index Model help SR stakeholders to better understand the scope of the assurance processes? and Why? Does the Content Index Model presented help to improve credibility of assured SR? and Why? Findings: Results obtained demonstrate that the updated Content Index Model improves SR stakeholders' understanding regarding the scope of the assurance processes conducted, thus reducing their expectation–performance gap on assurance processes and improving the credibility of SR. Participants also commented on the relationship among transparency, understand ability, trust and credibility. Research limitations/implications: First, participants were responsible for identifying the group that best represents his/her professional experience. The fact that participants have professional experience in more than one of the groups identified in this research (assurers, reporters and readers) could have impacted on their perceptions regarding the assurance process. Second, the interviews do not rely on practical experience with the updated Content Index Model, rather, they rely on participants' perceptions regarding the hypothetical use of this Content Index Model. Third, descriptive statistical analyses in this paper aim to illustrate participants' perceptions rather than to develop robust statistically significant conclusions. Fourth, the main author of this paper developed the Content Index Model, and this may have impacted the responses of the participants and/or the analysis of data. Also, the specific geographic area where interviews were conducted, the selection technique used and the non-statistical significance of the analyses presented in this paper must be carefully interpreted and cannot be generalised to a broader context based on this paper alone. Finally, interviews were developed and conducted before May 2013, before the GRI officially launched the GRI G4 Sustainability Reporting Guidelines. Practical implications: As the GRI is the most commonly used sustainability report framework to date, this study has the possibility to affect all companies that publish their sustainability reports based on the GRI framework and all assurance providers currently providing assurance services for such report. Also, findings would be very useful for sustainability reports' readers worldwide. Originality/value: As sustainability reports are the most common instruments used by organisations to provide accountability about the environmental and social performance, and assurance is the most common instrument used by organisations to improve credibility of such reports; it is important to assess whether those instruments are achieving their goals and understand the role played by the GRI G4 Content Index Model in this context. As the GRI G4 was recently launched, there is no study published yet assessing the effectiveness of its new content index model.